2020
DOI: 10.1530/erc-19-0483
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary poorly differentiated NECs, including molecular and immune aspects

Abstract: Patients with extrapulmonary poorly differentiated neuroendocrine carcinomas (EP-PD-NECs) have a poor prognosis. Surgery is offered for those with localised disease, but the majority of patients present with advanced disease. Treatment strategies adopted are analogous to that of high grade NECs of the lung, with platinum/etoposide-based regimens advocated in the first-line setting for advanced disease. There is no standard second-line therapy. Research into their molecular and immune pathways may pave the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 96 publications
2
17
0
3
Order By: Relevance
“…This result correlates to other phase 2 studies showing RRs ranging from 5 to 17.9% [25,37,38]. On the contrary, some other phase 1 studies describing results of monotherapy with pembrolizumab have concluded that this was not effective in biomarker 5 Case Reports in Oncological Medicine unselected populations of patients with poorly differentiated extrapulmonary NECs, like the one by Mulvey et al, describing a median PFS of 58 days, with almost half of the study population (n = 14) presenting early progression (PD) before the first checkup [25,39,40]. Another phase 2 study of pembrolizumab as monotherapy (Keynote-158) in welldifferentiated NETs concluded that the PD-1 inhibitor was ineffective, with only 3% of the entire population studied (n = 107) presenting an objective partial radiographic response [41,42].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result correlates to other phase 2 studies showing RRs ranging from 5 to 17.9% [25,37,38]. On the contrary, some other phase 1 studies describing results of monotherapy with pembrolizumab have concluded that this was not effective in biomarker 5 Case Reports in Oncological Medicine unselected populations of patients with poorly differentiated extrapulmonary NECs, like the one by Mulvey et al, describing a median PFS of 58 days, with almost half of the study population (n = 14) presenting early progression (PD) before the first checkup [25,39,40]. Another phase 2 study of pembrolizumab as monotherapy (Keynote-158) in welldifferentiated NETs concluded that the PD-1 inhibitor was ineffective, with only 3% of the entire population studied (n = 107) presenting an objective partial radiographic response [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Among these, a phase 1b trial (Keynote-028) which included patients with advanced solid tumors in different locations treated with pembrolizumab as monotherapy described an objective response rate (RR) of 12% for advanced PD-L1-positive carcinoid patients, as well as a 6% RR, 27% 12-month progression-free survival (PFS), and 87% overall survival (OS) for pancreatic NEC patients [26,29,35,36]. This result correlates to other phase 2 studies showing RRs ranging from 5 to 17.9% [25,37,38]. On the contrary, some other phase 1 studies describing results of monotherapy with pembrolizumab have concluded that this was not effective in biomarker 5 Case Reports in Oncological Medicine unselected populations of patients with poorly differentiated extrapulmonary NECs, like the one by Mulvey et al, describing a median PFS of 58 days, with almost half of the study population (n = 14) presenting early progression (PD) before the first checkup [25,39,40].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The genetic landscape of GEP-NEC is incompletely characterised, but it is clear that mutations in TP53, KRAS, PIK3CA/PTEN, or BRAF play an important role in malignant transformation and progression (reviewed in [25,26]). Girardi et al [27] performed a systematic review on this topic and identified 33 relevant studies.…”
Section: Biology Of Neuroendocrine Neoplasmsmentioning
confidence: 99%